Microbial consortia from residential wastewater for bioremediation of phenol in a chemostat - Jusoh, Norhani (Penerbit UTM Press, 2008)
The study aimed at evaluating the potential of employing microbial consortia from residential wastewater to degrade phenol, a common industrial pollutant. The consortia was subjected to high shock loads and different levels of phenol in continuous cultures. In the shock load study with 1000 ppm phenol in a 1.5 litre working volume chemostat, the culture with prior acclimatization to phenol demonstrated 17 times higher affinity towards phenol (i.e. Ks = 173 ppm). This resulted in double growth rate (Âµmax=Dc=0.04 h-1) compared to non-acclimatized culture. However, the levels of phenol reduction in both cases were almost identical, approximately 60%. This indicated that the performance of different types of bacteria present in the non-acclimatized culture which was comparable to the acclimatized culture although with less number of microbe types. The effects of two loading concentrations, namely 200 ppm and 1000 ppm were examined at constant dilution rate of 0.02 h-1. The feeding of 200 ppm exhibited 97% of phenol reduction in comparison to only 57% of 1000 ppm. This result reconfirmed the inhibitory effect of phenol reduction at concentration above 500 ppm as previously determined in batch culture. The study has successfully established key operating parameters and provided a useful guideline for future up-scaling studies and site trials.